A proteção do patrimônio público e a aplicação do Instituto da Desconsideração da Personalidade Jurídica na Justiça do Trabalho: uma visão republicana - Silva, Paulo Rogério Bueno da (2021)
The hiring of human resources, through an intermediary, called an outsourced company, is routine for the Public Administration. Non-payment of labor funds causes losses to workers who file complaints against the company and the State. With the merits of the cases, the company is ordered to pay the amounts owed, and the State is subsidiarily responsible for the respective payment in case of default. If the company's assets are not located to pay the worker, much less will assets be located to reimburse the amounts spent by the State, which will pay the debt as a subsidiary debtor. How to solve this problem? How to guarantee compliance with labor responsibility without affecting due legal process and making it possible to protect the republican principle of protection of public assets? From the perspective of this study, it is important to apply, still in the cognitive phase of the process, the new Institute for the Disregard of Legal Personality provided for in articles 133 to 137 of the new Code of Civil Procedure and article 855-A of the Consolidation of Labor Laws, and its impact on the patrimonial satisfaction of the Public Entity on the assets of the outsourced company’s partners. Furthermore, from the perspective of this work, the alternatives that both the Consumer Protection Code and the Civil Procedure Code provide for the search for assets in partners' assets in the event of irregular dissolution and non-payment of funds must be applied in an analogous manner. labor. The method to be used to carry out the proposed Dissertation will be hypothetical-deductive, being done through research based on bibliographical review and jurisprudential research, conceptualizing and analyzing the objects of this study.